Some considerations about the M|G|? queue approximation by a Markov renewal process - Ferreira, M. A. M. (Information Sciences and Computing, 2013)
Some M|G|? queue systems interesting quantities values approximations, obtained through the consideration of an adequate Markov renewal process, are presented and studied.